TARGET DOMAINS OF AIR 'WATER' IN INDONESIAN PROVERBS - I Dewa Putu Wijana (International Conference on Social and Islamic Studies, 2021)
This article deals with various target domains possibly represented by the source domain air 'water' contained in Indonesian proverbs. By observing Indonesian proverbs using word air extracted from 770 Peribahasa Indonesia (770 Indonesian Proverbs), it is found that this word is possibly used to represent at least 9 kinds of target domains. Those are  human character, work and activity, sadness and happiness, badness and goodness, help and things, event, place, personal relation, and words have been uttered.